QUALITY LEARNING FOR POSITIVE AGEING : Voice of Older Learners - Potter, Alan (Alan S.) (Routledge, 2024)
"Quality Learning for Positive Ageing explores the views of older adult learners to understand the factors that contribute to 'quality' in later-life learning and how these relate to wellbeing, positive ageing and gaining protection against cognitive decline"--